(untitled) (Veterinary Science, 2017)
Although the tuberculin test is the official diagnosis of bovine tuberculosis, the existence of false positives and false negatives is recognized; then, the interest in environmental mycobacteria as responsible for interspecific reactions is established. The objective of this study was to evaluate the association between the intradermal reaction used in the diagnosis of bovine tuberculosis employing bovine and avian PPD with pathological and bacteriological findings and, on the other hand, assess the possible cross-reaction with environmental mycobacteria using PPD prepared with Mycobacterium fortuitum and M. phlei (PPDs) isolated from soils from La Pampa (Argentina). Fifty (50) bovines were inoculated in the neck with bovine and avian tuberculin and two sensitines made with two strains of environmental mycobacteria (M. fortuitum and M. phlei); 72 hs later the reading and the subsequent necropsy of positive reacting and two nonreacting animals for each positive bovine to any of the PPD were made. 6% of theanimals reacted positively to bovine PPD, 2% reacted to the avian PPD and 16% did suspiciously to environmental mycobacteria. Of the 3 animals which reacted positively to bovine PPD, in two of them M. bovis was isolated and histopathological correlation was observed. No association in the diagnosis of intradermal reaction and in the parameters established by applying avian PPD was found. Although some animals displayed a mild suspicious reaction to environmental PPDs, both necropsy and histopathological and bacteriological studies showed no association with tuberculosis or mycobacteriosis.